Clocking In Time to Gate Memory Processes: The Circadian Clock Is Part of the Ins and Outs of Memory - Oliver Rawashdeh; Rex Parsons; Erik Maronde (Neural Plasticity)
Learning, memory consolidation, and retrieval are processes known to be modulated by the circadian (circa: about; dies: day) system. The circadian regulation of memory performance is evolutionarily conserved, independent of the type and complexity of the learning paradigm tested, and not specific to crepuscular, nocturnal, or diurnal organisms. In mammals, long-term memory (LTM) formation is tightly coupled to de novo gene expression of plasticity-related proteins and posttranslational modifications and relies on intact cAMP/protein kinase A (PKA)/protein kinase C (PKC)/mitogen-activated protein kinase (MAPK)/cyclic adenosine monophosphate response element-binding protein (CREB) signaling. These memory-essential signaling components cycle rhythmically in the hippocampus across the day and night and are clearly molded by an intricate interplay between the circadian system and memory. Important components of the circadian timing mechanism and its plasticity are members of the Period clock gene family (Per1, Per2). Interestingly, Per1 is rhythmically expressed in mouse hippocampus. Observations suggest important and largely unexplored roles of the clock gene protein PER1 in synaptic plasticity and in the daytime-dependent modulation of learning and memory. Here, we review the latest findings on the role of the clock gene Period 1 (Per1) as a candidate molecular and mechanistic blueprint for gating the daytime dependency of memory processing.